과냉각 액체 영역에서의 변형거동을 이용한 벌크 비정질 합금의 미세성형 기술 개발 - 옥명렬; 서진유; 홍경태 (한국소성가공학회, 2004)
Recently, various bulk metallic glasses (BMGs) having good mechanical and chemical properties were developed. BMGs can easily be deformed in the supercooled liquid region, via viscous flow mechanism. By using the viscous flow, the very low pressure is needed to deform the materials. In this study, we investigated the structural transition and deformation behavior of Vitreloy 1(Zr41.2Ti13.8Cu12.5Ni10Be22.5) using TMA and DSC. We applied the results to the micro forming process. The forming condition was chosen based on the viscosity data from TMA, and Si wafer with micro patterns on the surface was used as a forming die. The deformed surface was analyzed by SEM and 3D Surface Profiling System. The alloy showed good replication of the patterns. Quantitative measurement of roughness was useful to evaluate the replication. Surface condition of the deformed surface was determined by the initial surface condition.